Model for quality of life evaluation of NUTS 2 regions with rule-based systems - Šanda, Martin; Křupka, Jiří (Univerzita Pardubice, 2018)
This article deals with NUTS 2 regions quality of life (QL) evaluation for the Visegrad Group in year 2015 developed by means of rules based methods. QL evaluation is a phenomenon, topical issue, dealt with by a large number of institutions and organizations. Approaches to QL evaluation however differ and there exists a whole range of indicator sets and methodologies for QL evaluation. The evaluation is based on Eurostat methodology for QL evaluation in this article. The QL evaluation works with official indicators of this methodology and uses rule-based systems methods: modification of Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) - fuzzy TOPSIS (fTOPSIS), fuzzy inference system (FIS) and Casebased Reasoning (CBR) and with using pre-defined fuzzy sets (FSs). The objective of this article is to create a model for QL evaluation based on utilization of the abovestated methods, comparing results of the individual methods and the total results of such QL evaluation. Another objective of this article is to achieve fairness supported by this model – the results from this model shall serve as recommendations for provision of subsidies for regional development including the definition for what area such subsidy should be used.
Keywords: case-based reasoning; fuzzy inference system; fuzzy sets; quality of life; NUTS 2 regions; TOPSIS; C69; D89; H89; R59